Manipulation of Cell Cultures by Means of Holographic Visual Feedback - Varol, Rahmetullah; Aydemir, Gizem; Kamisli, Barkin Gonenc; Omeroglu, Sevde; Demircali, Ali Anil; Karavelioglu, Zeynep; Baskin, Yasemin; Uvet, Huseyin (IEEE, 2020)
In this study we present a novel untethered micro tool that is able to accomplish minimally invasive micro manipulation tasks in 2D and 3D cell cultures. We demonstrate the proposed system for targeted drug delivery, cell translation and mechanical cell stimulation applications. Due to the ability of the proposed system to control the motion of the micro tool in 6 DOF and obtain depth information through holographic visual feedback, we show that the microtool can be manipulated in a way such that the sample cell culture will go negligible mechanical stress. We show that the proposed system can be used for a variety of micro manipulation tasks without effecting the sample in question.
Keywords: Automation & Control Systems; Engineering; Science & Technology - Other Topics; Robotics